The treatment with trandolapril and losartan attenuates pressure and volume overload alternations of cardiac connexin-43 and extracellular matrix in Ren-2 transgenic rats - Sykora, Matus; Kratky, Vojtech; Cervenka, Ludek; Kopkan, Libor; Tribulova, Narcis; Szeiffova Bacova, Barbara (Scientific reports, 2023)
Heart failure (HF) is life-threatening disease due to electro-mechanical dysfunction associated with hemodynamic overload, while alterations of extracellular matrix (ECM) along with perturbed connexin-43 (Cx43) might be key factors involved. We aimed to explore a dual impact of pressure, and volume overload due to aorto-caval fistula (ACF) on Cx43 and ECM as well as effect of renin-angiotensin blockade. Hypertensive Ren-2 transgenic rats (TGR) and normotensive Hannover Sprague-Dawley rats (HSD) that underwent ACF were treated for 15-weeks with trandolapril or losartan. Blood serum and heart tissue samples of the right (RV) and left ventricles (LV) were used for analyses. ACF-HF increased RV, LV and lung mass in HSD and to lesser extent in TGR, while treatment attenuated it and normalized serum ANP, BNP-45 and TBARS. Cx43 protein and its ser368 variant along with PKCε were lower in TGR vs HSD and suppressed in both rat strains due to ACF but prevented more by trandolapril. Pro-hypertrophic PKCδ, collagen I and hydroxyproline were elevated in TGR and increased due to ACF in both rat strains. While SMAD2/3 and MMP2 levels were lower in TGR vs HSD and reduced due to ACF in both strains. Findings point out the strain-related differences in response to volume overload. Disorders of Cx43 and ECM signalling may contribute not only to HF but also to the formation of arrhythmogenic substrate. There is benefit of treatment with trandolapril and losartan indicating their pleiotropic anti-arrhythmic potential. It may provide novel input to therapy.
Keywords: potkani Sprague-Dawley; potkani transgenní; extracelulární matrix; Rats; Blood Pressure; Connexin 43; Heart Failure; Hypertension; Animals; píštěle; losartan; Extracellular Matrix; zvířata; Rats, Transgenic; hypertenze; Renin; krevní tlak; Fistula; krysa rodu Rattus; renin; konexin 43; srdeční selhání; Rats, Sprague-Dawley; Losartan